A study of consumer buying behaviour towards E-pharmacies in Delhi NCR. (7th May 2021) - Agarwal, Sumit; Bhardwaj, Garima
Background: Though E-Commerce is not a new concept to the world and even not to Indian markets but still buying and selling of medicines online is a new concept in Indian pharmaceutical business segment. Now a day's E-Pharmacy is receiving great consideration from the Indian investors and the government. There are various benefits which online pharmacies are offering to the customers like better price, ease of order, availability of brands, ease to compare etc. but there are also many issues related with online purchase of medicines including reliability, payment and security issues, chances of getting wrong order, non availability of prescribed medicines, problem in return of medicines, sale of substandard merchandise etc. Globally very less study is done on E-Pharmacy and especially in India there is very few studies on customer buying behaviour for online pharmacy. This study was done to find out customer perception towards online pharmacies and also access their satisfaction level on various benefits associated with E-Pharmacy and also to access their satisfaction level on various issues associated with E-Pharmacy.